HIV Seroprevalence and Risk Exposure Categories Among Clients Attending Sexually Transmitted Disease Clinics, Miami-Dade County, Florida, 1990-1999 - Marlene LaLota; Luis Miguel Garcia; Eduardo Valverde; Melinda Waters; Rodolfo Boucugnani; Thomas Liberti (University of North Florida, 2005)
The purposes of this study were to: (1) estimate the prevalence of HIV in sexually transmitted disease (STD) clinic populations; (2) assess risk exposure categories associated with HIV seropositivity; (3) monitor trends; and (4) supply data to inform and evaluate HIV prevention programs. Blood specimens were obtained from clients having routine serology at their initial visit for a new disease episode. Four clinics in Miami-Dade County participated in the 1990-1999 unlinked (blinded) seroprevalence survey. Specimens routinely collected for other purposes were stripped of identifiers and tested for antibodies to HIV-1. Demographic and risk information was gathered before testing. Tests results and data collection forms were forwarded to the Miami-Dade County Health Department (MDCHD), where they were scanned and entered into a database. We analyzed data from 41,354 specimens in relation to demographics, selected STDs, and HIV risk exposure categories. Overall HIV seroprevalence was 7.5% with a significantly higher infection rate for men (8.3%) compared to women (6%). Among those reporting heterosexual contact as their only risk, the infection rate (4.9%) was 13 times the estimated national HIV infection rate (0.36%). HIV rates declined over nine years (from 10.8% to 5.8%) with significant downward trends observed for men and women; and for whites, blacks, and Hispanics. We found a significantly higher HIV rate for ulcerative STDs (9.4%) compared with non-ulcerative STDs (6.2%) for both males and females. Higher HIV rates were also found among those diagnosed with multiple STDs (15.4%) compared to those in either the ulcerative or non- ulcerative STD category. In conclusion, we strongly emphasize the need for assessing HIV infection in STD patients, and STD infections in HIV-infected patients.